USE OF FOLEY’S CATHETER AND PROSTAGLANDIN F-2 ALPHA IN SECOND TRIMESTER TERMINATION OF PREGNANCY - Islam, Ansa; Abbasi, Aziz un Nisa; Sarwar, Iram (Journal of Ayub Medical College Abbottabad, 2006)
Background: Termination of pregnancy (TOP) in the second trimester is associated with three to five times higher risk of maternal morbidity and mortality than termination during first trimester. The main concern of obstetrician is to provide the most effective and safest regimen which combines the shortest expulsion interval with least side effects. This study was undertaken to compare the use of Foley’s catheter with extra-amniotic instillation of PGF2 alpha for second trimester TOP so that a choice of the safer and cost-effective method could be available. Methodology: The study was conducted in Department of Obstetrics and Gynecology Unit ’˜B’ at Ayub Teaching Hospital Abbottabad between August 2003 and July 2004. Sixty patients recommended for TOP (missed abortion or anencephalic fetus confirmed on ultrasonography) were randomly allocated into two groups. In group ’˜A’, Foley’s catheter alone was used while in group ’˜B’ extra amniotic instillation of Prostaglandin F-2 alpha (PGF2 alpha) was done via a Foley’s catheter. After expulsion of catheters in both cases oxytocin infusion containing 30 units were started till the expulsion of fetus, placenta and membranes. The mean induction to expulsion time and the mean induction to delivery time for both groups were noted as well as total cost of treatment. Results: Difference in time interval with regard to induction to expulsion time of catheter and induction to delivery time between the two groups was significant being 3 hours and 5 hours respectively less in group ’˜B’ (p < 0.001); however only 25% of patients in group ’˜B’ had a significant short induction to delivery time as compared to group ’˜A’. The difference in costs of treatment between the groups was also significant (p < 0.001). Conclusion: Use of PGF 2 alpha is preferred, though for poor patients Foley’s catheter may be used, but only in a tertiary care setting. Key Words: Dinoprost, Abortion, Labor onset, Uterine contraction, Cervical ripening, Balloon dilatation.